PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN HIGH ORDER THINKING PADA SISWA SMP - Ajeng Setiasih; Desy Lusiyana; Sumliyah sumliyah (Integral : Pendidikan Matematika, 2019)
This research is motivated by the low ability of students to think high in learning. The purpose of this study was to determine the improvement of high-level thinking skills of students who learned using the Project Based Learning model with conventional learning. This research is a quasi-experimental study. The research design used is Nonequivalent Control Group Design and Purposive Sampling sampling technique. The population is a class VIII student of SMPN 1 Tengah Tani Cirebon Regency Academic Year 2018/ 2019. The research sample involved eighth grade students, namely 35 class VIII B students as the experimental class and 35 class VIII C students as the control class. Based on the results of the Shapiro-Wilk normality test the pretest, posttest and N-Gain values ??were normally distributed and the results of the Levene’s Test homogeneity test the pretest, posttest and N-Gain scores were homogeneous. Then the mean posttest difference test using the Independent Sample t-Test Test produces sig values. (2-tailed) 0,000 <0,05, meaning that H0 is rejected. Furthermore, the N-Gain mean difference test with the Independent Sample t-Test was obtained the sig value. (1-tailed) <0.05, ie H0 is rejected. Whereas based on the results of the questionnaire scale using Mann Whitney U-Test produces Asymp values. Sig (2-tailed) 0,000 <0,05, ie H0 is rejected. The results showed that: (1) high order thinking students who learned using the Project Based Learning (PjBL) model were better than students who conventional learning; (2) the improvement of high-order thinking skills of students whose learning uses the Project Based Learning (PjBL) model is better than students who learn conventionally; (3) the response of students whose learning uses the Project Based Learning model is better than the students who learn conventionally. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan berpikir tingkat tinggi siswa dalam pembelajaran. Tujuan dari penelitian ini adalah untuk mengetahui peningkatan kemampuan berpikir tingkat tinggi siswa yang pembelajarannya menggunakan model Project Based Learning dengan pembelajaran secara konvensional. Penelitian ini merupakan penelitian kuasi eksperimen. Desain penelitian yang digunakan Nonequivalent Control Group Design dan teknik pengambilan sampelnya Sampling Purposive. Populasinya adalah siswa kelas VIII SMPN 1 Tengah Tani Kabupaten Cirebon Tahun Pelajaran 2018 / 2019. Sampel penelitian melibatkan siswa kelas VIII yaitu 35 siswa kelas VIII B sebagai kelas eksperimen dan 35 siswa kelas VIII C sebagai kelas kontrol. Berdasarkan hasil uji normalitas Shapiro-Wilk nilai pretes, postes dan N-Gain berdistribusi normal serta hasil uji homogenitas Levene’s Test nilai pretes, postes dan N-Gain bervariansi homogen. Kemudian uji perbedaan rerata postes mengunakan Uji Independent Sample t-Test menghasilkan nilai sig. (2-tailed) 0,000 0,05, artinya H0 ditolak. Selanjutnya uji perbedaan rerata N-Gain dengan Uji Independent Sample t-Test diperoleh nilai sig. (1-tailed) 0,05, yaitu H0 ditolak. Sedangkan berdasarkan hasil skala angket menggunakan Mann Whitney U-Test menghasilkan nilai Asymp. Sig (2-tailed) 0,000 < 0,05, yaitu H0 ditolak. Hasil penelitian menunjukkan bahwa: (1) kemampuan berpikir tingkat tinggi (High Order Thinking) siswa yang pembelajarannya menggunakan model Project Based Learning (PjBL) lebih baik daripada siswa yang pembelajarannya secara konvensional; (2) peningkatan kemampuan berpikir tingkat tinggi (High Order Thinking) siswa yang pembelajarannya menggunakan model Project Based Learning (PjBL) lebih baik daripada siswa yang pembelajarannya secara konvensional; (3) respon siswa yang pembelajarannya menggunakan model pembelajaran Project Based Learning lebih baik daripada siswa yang pembelajarannya secara konvensional